Population and Poverty as Determinants of the Human Development Index in East Luwu Regency - Azis, Azliya Aliana; Achsanuddin, A. Nur; Warda (Scimadly Publishing, 2025)
This study examines the influence of population size and poverty on the Human Development Index (HDI) in East Luwu Regency. Employing secondary time-series data covering 2014-2023, the research utilizes multiple linear regression analysis supported by classical assumption tests, with data processing performed using SPSS version 22. The empirical results reveal that neither population size nor poverty exerts a statistically significant effect on HDI, as indicated by significance levels exceeding 0.05 for both variables. These findings suggest that demographic expansion and poverty reduction alone are insufficient to drive substantial improvements in human development outcomes in the region. Instead, advancing HDI in East Luwu Regency requires more comprehensive policy approaches that prioritize investment in education, healthcare accessibility, and the overall quality of human resources. Theoretically, the study enriches development economics literature by underscoring regional disparities in HDI determinants, while practically, it offers evidence-based insights for local governments to formulate more targeted and effective strategies for enhancing human development.